Pengenalan Huruf Arab Berbasis Analogi Benda melalui Media ABATA bagi Anak Tunagrahita - Muhammad Syahri Romadhon; Titis Thoriquttyas; Yusuf Hanafi; Mohammad Ahsanuddin (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: Intellectually disabled children have difficulty understanding abstract things such as Arabic letters. An appropriate learning media that can help them learn is significantly needed. In addition, some Intellectually disabled children can only pronounce Arabic letters but do not know the shape of the Arabic letters. In this context, ABATA media associates and equates Arabic letters with surrounding objects in their form and pronunciation so that intellectually disabled children can know the form and pronunciation of Arabic letters. This research aims to describe the ABATA media and its effectiveness. This research uses narrative review by gathering data from various sources, analyzing and designing the media. ABATA media is designed based on visual media and adopts the analogy method by equating the form of objects with Arabic letters, and the pronunciation of Arabic letters is the same as the initial syllable of objects. Based on the search for various literature sources conducted by the researchers, ABATA media is predicted to be adequate for mentally disabled children in introducing Arabic letters. This is because the visual media and analogy methods that are the basis for developing the ABATA media have proven effective and acceptable to intellectually disabled children. Therefore, ABATA media is believed to make it easier to introduce the shape and pronunciation of Arabic letters. Keywords: Arabic letters, visual media, analogy, intellectual disability. Abstrak: Anak tunagrahita mengalami kesulitan dalam memahami hal yang bersifat abstrak, seperti huruf Arab sehingga diperlukan media yang dapat mengonkretkan hal tersebut. Selain itu, terdapat anak tunagrahita yang hanya mampu melafalkan huruf Arab namun tidak mengetahui bentuk huruf Arab tersebut. Dalam konteks ini, media ABATA mengaitkan dan menyamakan huruf Arab dengan benda-benda sekitar dalam bentuk dan pengucapannya agar anak tunagrahita mampu mengetahui bentuk sekaligus pelafalan huruf Arab. Penelitian ini bertujuan untuk mendeskripsikan media ABATA dan keefektifannya secara konseptual. Penelitian ini menggunakan metode narrative review dengan mencari berbagai sumber, menganalisis, dan kemudian mendesain media. Media ABATA dirancang berbasis media bergambar dan mengadopsi metode analogi dengan menyamakan bentuk benda dengan bentuk huruf Arab. Adapun pelafalan huruf Arab disamakan dengan suku awal benda. Berdasarkan penelusuran berbagai literatur yang telah dilakukan oleh peneliti, media ABATA diprediksikan efektif untuk diterapkan kepada anak tunagrahita dalam mengenalkan huruf Arab. Hal ini didasarkan pada kenyataan bahwa media bergambar dan metode analogi yang menjadi basis pengembangan media ABATA ini terbukti efektif dan mampu diterima oleh anak tunagrahita. Oleh karena itu, media ABATA diyakini mampu mempermudah dalam pengenalan bentuk sekaligus pelafalan huruf Arab. Kata kunci:  huruf Arab, media bergambar, analogi, tunagrahita